Assessment of benefits and risks of sodium-glucose co-transporter 2 inhibitors in metabolic complications - Oliveira, Ricardo Filipe Silva de (2019)
Sodium-glucose co-transporter 2 (SGLT2) inhibitors (e.g. canagliflozin, dapagliflozin, empagliflozin, ertugliflozin) have been recently approved for type 2 diabetes mellitus (T2DM) treatment, a metabolic disease affecting a huge number of persons worldwide. Subsequently to their marketing authorization, various clinicals trials involving SGLT2 inhibitors (iSGLT2) drugs have joined important information that, besides contributing to updated T2DM management guidelines, have also reported relevant data hinting for their potential to afford nephroprotection. In the present review, we proposed to take a step back into in vivo and in vitro studies and gather pre-clinical evidence aimed to better understand the mechanisms underlying iSGLT2 renal protection. Literature review was performed for cellular and experimental animal models of diabetic nephropathy, chronic kidney disease (CKD) and acute kidney injury (AKI) receiving iSGLT2 treatment. Data extraction was performed from primary research papers of quantitative design published in the period between January 2013 and December 2018. Only publications relevant for iSGLT2 nephroprotection were considered. Publications selected in the present review were assessed for statistically relevant parameters related to nephroprotection. A total of 33 publications were included in the present review, corresponding to 42 experimental models of kidney disease. In total, 546 parameters related to distinct kidney disease models and corresponding iSGLT2 treatment outcomes were analyzed. Overall, iSGLT2 treatment was associated with a reversal of systemic pathophysiological features underlying T2DM, kidney morphology, kidney function (serum, urine and tissue biomarkers) and cellular and molecular mechanisms underlying renal injury (including inflammation, oxidative stress and apoptosis). These effects were observed in distinct kidney disease models. Nevertheless, worsening of disease severity was not absent and should be considered. Oxidative stress, inflammation and fibrosis are relevant processes that precipitate progression of kidney diseases and deteriorate kidney function and morphology. SGLT2 blockade was chiefly associated with the mitigation of these processes, very likely due to their ability to improve hemodynamic and metabolic features, and to reduce glucotoxicity. However, severe metabolic shifts may, in particular circumstances, hinder iSGLT2 benefic renal effects. Understanding the finetune of iSGLT2 mechanism of action can be of the utmost importance to unequivocally disclose iSGLT2 nephroprotective potential while minimizing adverse events.